Analysis Of Land Disputes Arising From Land Procurement Activities In The Development Of Public Facilities And Infrastructure (Review of Law Number 2 of 2012 concerning Land Acquisition - Askolani Jasi; Evita Isretno Israhadi; Riswadi Riswadi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The phenomenon of the pros and cons of the Cipta Field or Omnibus Law regulations, for those who are pro, is the right solution to address the problem of overlapping laws and regulations in Indonesia. Whereas those who are against, think that the omnibus law plan is seen as an effort to delegitimize the rights of every sector of national life, especially regarding employment and other sectors that may be affected by its implementation. Thus, the implementation of the Omnibus Law must be seen from various aspects, including legal theory and more technical aspects of state administrative law in the Unitary State of the Republic of Indonesia